Acute Chagas Disease Outbreak among Military Personnel, Colombia, 2021 (2023)
We report an acute Chagas disease outbreak among soldiers in Colombia. Trypanosoma cruzi infection was confirmed through parasitology, serology, and molecular methods. Among 9 affected soldiers, 2 died; 7 were hospitalized and received benznidazole treatment, which produced favorable outcomes. Personnel patrolling rural areas in Colombia could be at increased risk for Chagas disease.